Bioelectricity generation in continuously-fed microbial fuel cell: Effects of anode electrode material and hydraulic retention time - Akman, Dilek; Cirik, Keyser; Ozdemir, Sebnem; Ozkaya, Bestamin; Cinar, Ozer (ELSEVIER SCI LTD, 2013)
The main aim of this study is to investigate the bioelectricity production in continuously-fed dual chambered microbial fuel cell (MFC). Initially, MFC was operated with different anode electrode material at constant hydraulic retention time (HRT) of 2 d to evaluate the effect of electrode material on electricity production. Pt electrode yielded about 642 mW/m(2) power density, which was 4 times higher than that of the MFC with the mixed metal oxide titanium (Ti-TiO2). Further, MFC equipped with Pt electrode was operated at varying HRT (2-0.5 d). The power density generation increased with decreasing HRT, corresponding to 1313 mW/m(2) which was maximum value obtained during this study. Additionally, decreasing HRT from 2 to 0.5 d resulted in increasing effluent dissolved organic carbon (DOC) concentration from 1.92 g/L to 2.23 g/L, corresponding to DOC removal efficiencies of 46% and 38%, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Continuous flow; Hydraulic retention time; Microbial fuel cell; Pt electrode; Ti-TiO2 electrode; WASTE-WATER TREATMENT; ELECTRICITY-GENERATION; MEDIATOR-LESS; PERFORMANCE; TECHNOLOGY; BIOENERGY; PH; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels